Treatment Options and Voice Outcomes for Patients With Unilateral Vocal Fold Paralysis After Thyroidectomy - Wen, Ming-Hsun; Wang, Chi-Te (Frontiers in Endocrinology, 2022)
Objectives: This study investigated the treatment options and clinical outcomes of voice therapy (VT), hyaluronic acid (HA) injection, autologous fat injection (FI), and medialization thyroplasty (MT) in patients with unilateral vocal fold paralysis (UVFP) after thyroidectomy. Study Design: Retrospective case series. Setting: A tertiary teaching hospital. Methods: This study included 51 patients with post-thyroidectomy UVFP who underwent VT (n = 20), HA injection (n = 14), FI (n = 12), or MT (n = 5) from January 2016 to June 2021. The treatment outcomes were evaluated using 10-item voice handicap index (VHI-10), maximal phonation time (MPT), and auditory perceptual rating using GRB scales (i.e., grade, roughness, and breathiness) before and 3 to 6 months after treatment. Results: Patients received HA injection presented a significantly shorter interval following thyroidectomy(mean: 4.6 months), followed by VT (6.7 months), FI (12.3 months), and MT (22.4 months). The results exhibited improvement in most of the outcomes after all of the four treatments. Additional comparisons indicated that VHI-10 scores improved the most among patients receiving MT, followed by HA, FI, and VT. The differences of MPT and GRB scores among the 4 treatment groups were non-significant. Conclusions: The results revealed that VT, HA, FI, and MT can all improve the voice outcomes of patients with post-thyroidectomy UVFP. The optimal treatment approach should be individualized according to the patient’s preference and vocal demand, and the interval between thyroidectomy and intervention.